Fashion Trend Forecasting Spirituality as an Inspiration in Creating Evening Party Dress Design Illustration Titled De Valeur - Alfitrah, Fauzan; Arifiana, Deny; Rahayu, Imami Arum Tri; Wiyono, Agus (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
De Valeur comes from the French word which means "Precious" and is the title of a work of evening dress design illustration which take an inspiration from by 2021/2022 fashion trend forecasting theme : Spirituality. Spirituality being depicted by the use of Indonesian traditional fabric which is woven fabric that becomes one of the idea for creating evening party dress design illustration. This is based on the fact that the Spirituality theme has characteristics such as classic and elegant impression, colors that tend to be earth tones, the use of natural materials, or even the use of traditional fabrics. The aim of this creation is to describe the process and the result of creating an evening party dress design illustration which applies fashion trend forecasting theme as an inspiration. This creation using the practice-led research method of craft arts, consisting of 4 stages which includes: (1) pre-design, (2) design, (3) Embodiment, and (4) presentation. The results of this research shows the process of creating evening dress design illustration which includes exploring idea, developing alternative designs, perfecting the chosen design and publishing the illustration which in line with practice-led method stages order. The result of this research is 1 piece of evening dress fashion design illustration front and back look titled "De Valeur" designed and inspired by the characteristics from Fashion Trend Forecasting Spirituality.